LB-10. Rapid Assessments of Non-Pharmaceutical Intervention Uptake and Population Mobility Patterns Elucidate SARS-Cov-2 Transmission Dynamics. (31st December 2020) - Wesolowski, Amy; Gibson, Dustin; Agarwal, Smisha; Lambrou, Anastasia; Kirk, Gregory; Labrique, Alain; Mehta, Shruti; Solomon, Sunil
Abstract: Background: Current mitigation strategies for SARS-CoV-2 rely on population-wide adoption of non-pharmaceutical interventions (NPIs). Monitoring NPI adoption, mobility patterns and their association with SARS-CoV-2 infection can provide key information for public health agencies and be used to calibrate transmission models. Methods: We used an online panel to accrue representative samples from Florida, Illinois, and Maryland (n=3, 009, approximately 1, 000 per state) from July 15–31, 2020 and capture socio-demographically and geographically resolved information about NPI adoption and mobility in the prior 2 weeks. Logistic regression was used to identify correlates of self-reported SARS-CoV-2 infection in the prior 2 weeks. Results: Overall, 96% reported traveling outside their home in the prior 2 weeks, the most common reason being to visit a grocery store/pharmacy (92%), followed by visiting friends/family (61%), and visiting a place of worship (23%); 22% reporting public transportation use. In total, 44% of respondents reported always practicing social distancing and 40% reported always using a mask indoors and outdoors. Overall, 74 (2.5%) reported testing positive for SARS-CoV-2 in the prior 2 weeks, with strong dose-response relationships between several forms of movement frequency and SARS-CoV-2 positivity. Variables capturing mobility were all highly correlated with one another, suggesting there are clusters of individuals who engage in multiple activities (Figure); 41% of positive cases engaged in all forms of mobility captured compared to 1% of those who did not test positive within the prior 2 weeks. Patterns of mobility and NPI uptake did not significantly differ by state; however, there were significant relationships with age, race/ethnicity, and gender. In multivariable models including adjustment for NPIs, significant relationships remained with public transportation, visiting a place of worship, and participating in outdoor group fitness activities. Figure. Heatmap depicting pairwise Spearman correlation coefficients between survey responses. Pairwise correlation coefficients are displayed in the boxes at intersection of any two variables. Questions were asked with respect activities in the prior 2 weeks. Conclusion: NPI adoption and mobility did not vary across these three states with variable policies and SARS-CoV-2 positivity rates. Rather, associations with recent positivity appear to be driven largely by mobility patterns and engagement in activities where NPI use may be challenging or inconsistent. Disclosures: Shruti Mehta, PhD, MPH, Gilead Sciences (Other Financial or Material Support, Speaker) Sunil Solomon, MD, PhD, MPH, Abbott Diagnostics (Grant/Research Support)Gilead Sciences (Grant/Research Support, Advisor or Review Panel member)